Avian influenza overview February – May 2021. (6th December 2021) - ,; ,; ,; Adlhoch, Cornelia; Fusaro, Alice; Gonzales, José L; Kuiken, Thijs; Marangon, Stefano; Niqueux, Éric; Staubach, Christoph; Terregino, Calogero; Aznar, Inma; et al.
Abstract: The 2020‐2021 epidemic with a total of 3, 555 reported HPAI detections and around 22, 400, 000 affected poultry birds in 28 European Countries appears to be one of the largest and most devastating HPAI epidemics ever occurred in Europe. Between 24 February and 14 May 2021, 1, 672 highly pathogenic avian influenza (HPAI) virus detections were reported in 24 EU/EEA countries and the UK in poultry (n=580), and in wild (n=1, 051) and captive birds (n=41). The majority of the detections in poultry were reported by Poland that accounted for 297 outbreaks occurring in a densely populated poultry area over a short period of time, followed by Germany with 168 outbreaks. Germany accounted for 603 detections in wild birds, followed by Denmark and Poland with 167 and 56 detections, respectively. A second peak of HPAI‐associated wild bird mortality was observed from February to April 2021 in north‐west Europe. The observed longer persistence of HPAI in wild birds compared to previous years may result in a continuation of the risk for juveniles of wild birds and mammals, as well as for virus entry into poultry farms. Therefore, enhanced awareness among farmers to continue applying stringent biosecurity measures and to monitor and report increases in daily mortality and drops in production parameters, are recommended. Sixteen different genotypes were identified to date in Europe and Russia, suggesting a high propensity of these viruses to reassort. The viruses characterized to date retain a preference for avian‐type receptors; however, transmission events to mammals and the identification of sporadic mutations of mammal adaptation, indicate ongoing evolution processes and possible increased ability of viruses within this clade to further adapt and transmit to mammals including humans. Since the last report, two human infections due to A(H5N6) HPAI were reported from China and Laos and 10 human cases due to A(H9N2) low pathogenic avian influenza (LPAI) virus identified in China and Cambodia. The risk of infection for the general population in the EU/EEA is assessed as very low and for occupationally exposed people low . People exposed during avian influenza outbreaks should adhere to protection measures, strictly wear personal protective equipment and get tested immediately when developing respiratory symptoms or conjunctivitis within 10 days after exposure.